AAV5-miHTT gene therapy demonstrates suppression of mutant huntingtin aggregation and neuronal dysfunction in a rat model of Huntington’s disease - Miniarikova, J (Gene Ther, 2017)
Huntington’s disease (HD) is a fatal progressive neurodegenerative disorder caused by a mutation in the huntingtin (HTT) gene. To date, there is no treatment to halt or reverse the course of HD. Lowering of either total or only the mutant HTT expression is expected to have therapeutic benefit. This can be achieved by engineered micro (mi)RNAs targeting HTT transcripts and delivered by an adeno-associated viral (AAV) vector. We have previously showed a miHTT construct to induce total HTT knock-down in Hu128/21 HD mice, while miSNP50T and miSNP67T constructs induced allele-selective HTT knock-down in vitro. In the current preclinical study, the mechanistic efficacy and gene specificity of these selected constructs delivered by an AAV serotype 5 (AAV5) vector was addressed using an acute HD rat model. Our data demonstrated suppression of mutant HTT messenger RNA, which almost completely prevented mutant HTT aggregate formation, and ultimately resulted in suppression of DARPP-32-associated neuronal dysfunction. The AAV5-miHTT construct was found to be the most efficient, although AAV5-miSNP50T demonstrated the anticipated mutant HTT allele selectivity and no passenger strand expression. Ultimately, AAV5-delivered-miRNA-mediated HTT lowering did not cause activation of microglia or astrocytes suggesting no immune response to the AAV5 vector or therapeutic precursor sequences. These preclinical results suggest that using gene therapy to knock-down HTT may provide important therapeutic benefit for HD patients and raised no safety concerns, which supports our ongoing efforts for the development of an RNA interference-based gene therapy product for HD.